The Effects of Mass Communication on Changes of Public Attitudes and Behavior in the Digital Era - Hendra Prasetia; Muhammad Fahmi Syihab; Umi Halwati (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2025)
Through social media and online platforms that reach a wide audience, the development of information technology in the digital era has significantly changed the pattern of mass communication. Every message in the media does not stop at conveying information but can also have an impact on the audience. This impact is known as the mass communication effect, which has become a major focus in communication studies. How audiences think, act, and behave is largely influenced by the media. This study aims to discuss the effects of mass communication on changes in attitudes and behavior, focusing on three main domains of human psychology: cognitive, affective, and conative. This research use descriptive qualitative approach and content analysis to emphasize the effects of mass communication on the psychological realm. The results of this study demonstrate that digital media has the ability to construct knowledge, influence feelings, and drive audience action quickly and dynamically. This research confirms that the role of social media as a strategic space requires critical study, especially on the effects of mass communication on understanding the relationship between media dynamics, society, and the process of forming an opinion that has an impact on changes in people's attitudes and behavior.